Better tolerance of preservative-free latanoprost compared to preserved glaucoma eye drops: the 12-month real-life FREE study - Economou MA (Dove Medical Press, 2018)
Mario A Economou,1 Helene Kolstad Laukeland,2,3 Iwona Grabska-Liberek,4 Jean-François Rouland5 1Anterior Segment Department, St Erik’s Eye Hospital, Karolinska Institute, Stockholm, Sweden; 2Department of Ophthalmology, University Hospital, Trondheim, Norway; 3Department of Laboratory Medicine, Norwegian University of Science and Technology, Trondheim, Norway; 4Department of Ophthalmology, Ophthalmology Clinic Postgraduate Centre of Medical Education, Warszawa, Poland; 5Department of Ophtalmology, Claude Huriez Hospital, University Hospital, Lille, France Background: Lack of efficacy due to bad compliance caused by intolerance issues is the main reason for a change to a better tolerated ocular treatment, such as using preservative-free (PF) eye drops.Aim: To assess the efficacy and local tolerance after 12 months and patient satisfaction regarding local treatment tolerance and handling at inclusion and after 6 months of PF latanoprost compared to preserved glaucoma eye drops.Methods: This was an international, prospective, and observational real-life study. Up to three visits, one at inclusion and two follow-up visits (one after 6 and one after 12 months) were planned. Efficacy, local tolerance, and patient satisfaction were the main evaluation criteria.Results: Data from 721 patients were available for the statistical analysis. Overall, 64.8% (467/721) of patients switched treatment before inclusion: 62.2% in the preserved and 68.9% in the PF latanoprost group. IOP values were similar between PF latanoprost and preserved eye drops and remained stable at all visits. Ocular signs and symptoms improved after switching to PF latanoprost; the prevalence of conjunctival hyperemia was significantly lower (P=0.0015) at both follow-up visits. At follow-up visit 1, 49.5% of the patients who switched to PF latanoprost decreased or stopped the use of artificial tears. Satisfaction regarding tolerance in patients using PF latanoprost improved significantly after the switch from preserved eye drops to PF latanoprost (88.9% and 42.5%, respectively, P<0.0001).Conclusion: This first real-life study showed that PF latanoprost was as efficacious but better tolerated than preserved eye drops over a sustained period of 12 months, while providing a significantly higher patient satisfaction and potentially allowing improvement in the patient’s daily life. Keywords: glaucoma, prostaglandins, preservative-free latanoprost, patient satisfaction, conjunctival hyperemia, ocular surface diseases